Physical-chemical parameters and zooplankton community structure of the Odra oxbow in the spring season - Ławniczak, Jacek; Świdnicki, Kasper; Wiśniewska, Małgorzata; Bodzioch, Adam; Kuczyńska-Kippen, Natalia (Department of Water Protection, Faculty of Biology, Adam Mickiewicz University, 2008)
The examination of the distribution of rotifers and crustaceans between particular stations located within vegetated (zones of helophytes and nymphaeids) and unvegetated (open water area) zones of an oxbow lake situated within the River Odra valley was carried out during the period of high water level in April of 2007. The obtained results revealed a considerable species diversity along with low densities of particular zooplankton species, which are characteristic features for slightly humic waters. The most diverse species composition of rotifers was found in the littoral zone of the studied water body. This was probably due to the heterogeneity of the macrophyte-dominated area. Additionally, the presence of fish in the investigated oxbow lake may have been responsible for finding the greatest abundance of Crustacea in the zones dominated by aquatic vegetation.
Keywords: Rotifers; Crustaceans; Ponds; Species diversity; Macrophytes